Web-based user interface prototyping and simulation - Faria, Paulo Cristiano Pinheiro (2014)
PVSio-web is a platform for the simulation and prototyping of user interfaces that has been developed by researchers at Queen Mary University of London. This platform aims to reduce barriers to the use of PVS by users unfamiliar with formal methods. The main features of PVSio-web focus on creating, opening and saving projects, loading images and creating widget areas over them, and not least, editing PVS files. Editing files is limited to only one file per project and the platform also does not have image editing features. PVSio-web can then be improved by implementing features to support editing multiple files and images (such as cropping and resizing). The interaction areas can also be improved to thereby enhance the quality of the prototype, by adjusting the precision of the dimensions and positioning of the area relatively to the image. In this dissertation the improvements achieved on the editing of files, images and interaction areas in PVSio-web, in order to increase the quality and optimize its use in a real environment, are described.